Impacts of Human Activities on Tree Species Composition Along the Forest Savanna Boundary in Nigeria - Christiana Ndidi Egbinola (Indonesian Journal of Geography, 2015)
The study investigated the tree species composition along the forest-savanna boundary in Oyo state of Nigeria with the aim of assessing the impact of human activities on the floristic composition. A transect was placed along the study area and species data was collected from quadrats placed in study plots within different study sites. Detrended Correspondence Analysis (DCA) was used to determine vegetation assemblages, while both correlation and the analysis of variance (ANOVA) were used to show the relationship between species in the different study sites. Results of the DCA revealed three species assemblages, an area with only forest species, another with only savanna species and a third with both forest/savanna species. ANOVA results further revealed that within the forest and savanna assemblages, species in mature and successional sites were alike. The study therefore revealed that human activities’ within the region is leading to the establishment of savanna species and an elimination of forest species.